Implementation of Marketing Strategy in Efforts to Increase Sales of Kerosene Stove Products at Bintang Tiga Home Industry in Malang City - Kristianto Orlando Yusran; R Y Susanto; Warter Agustim (IRDH International Journal of Social Sciences & Humanities, 2026)
Marketing strategy is a plan that outlines the company's expectations of the impact of various marketing activities or programs on the demand for its products or product lines in a particular target market. The aim of this study is to determine how marketing strategies increase sales of stove products. This type of research uses a descriptive method with a qualitative approach  Data analysis techniques using SWOT Analysis. The results show that the market development strategy has the highest TAS value with a value of 7.03, making it the most appropriate priority strategy to be implemented by the Bintang Tiga Kerosene Stove Home Industry. The market development strategy was chosen because it was considered most capable of utilizing the internal strengths and external opportunities of the Bintang Tiga Home Industry. Marketing strategies have a very important role in increasing sales of kerosene stove products in Home Industry Bintang Tiga Malang. Amid competition from modern stoves like gas and electric stoves, kerosene stoves still have a market opportunity, particularly in certain regions and among consumer groups with specific needs and purchasing power.